Endoscopic, Endonasal Transsphenoidal Surgery for Tumors of the Sellar and Suprasellar Region: A Monocentric Historical Cohort Study of 369 Patients - Van Gerven, Laura; Qian, Zhen; Starovoyt, Anastasiya; Jorissen, Mark; Meulemans, Jeroen; van Loon, Johannes; De Vleeschouwer, Steven; Lambert, Julie; Bex, Marie; Vander Poorten, Vincent (Frontiers in Oncology, 2021)
Background: The endoscopic endonasal transsphenoidal approach (EETA) is an established technique for the resection of a large variety of benign sellar and suprasellar lesions, mostly pituitary adenomas. It has clear advantages over the microscopic approach, like a superior close-up view of the relevant anatomy and the tumor-gland interface, an enlarged working angle, as well as an increased panoramic vision inside the surgical area. We have been performing the EETA for over a decade, and this study will focus on perioperative and postoperative outcomes and complications, and their association with the learning curve. Material and methods: All patients in our tertiary referral center (n=369) undergoing an EETA for a lesion of the sellar and suprasellar region between January 1st 2008 and December 31st 2018 were included, and data were retrospectively retrieved from the electronic patient records. Results: Median follow-up after surgery was 55 months. Pituitary adenomas (n=322) were the most frequent pathology. Headache (43,4%) and loss of vision (29,3%) were the most common presenting symptoms. Median procedure duration was significantly longer during the initial 5 years (106 minutes versus 79 minutes; p<0,0001), but incidence of peri- and postoperative CSF leaks in the early years was not significantly higher. Knosp grade > 2 was associated with perioperative CSF leak (p=0,002), and perioperative CSF leak was associated with postoperative CSF leak (p<0,001). Almost all cases of meningitis were preceded by a postoperative CSF leak. In 22,4% of patients, tumor recurrence required additional therapy. Perioperative (iatrogenic) mortality was 0,8%. The overall hospital stay decreased over time from an average of 7 to 5 days and the case load increased yearly (p=0,015). Conclusion: The EETA is an excellent technique with complication rates comparable to or even lower than those in large microsurgical series in the literature. EETA has a significant learning curve, affecting the procedure duration. Throughout the first 10 years following the transition from the microscopic approach to the EETA in our cohort, the caseload increased and hospital stay was reduced, whilst no increase in peri- and post-operative complications was observed.